2011
DOI: 10.1007/s00262-011-0992-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immunocompetent cells after interstitial laser thermotherapy of breast cancer

Abstract: BackgroundLocal tumour destruction has been shown to give rise to changes in immunocompetent cells. The aim of this study was to describe the effect of interstitial laser thermotherapy (ILT) of breast carcinoma in the tumour and in regional lymph nodes.MethodsSeventeen women that underwent radical surgical excision after non-radical ILT were studied. ILT was performed at a steady-state temperature of 48°C for 30 min. Surgical excision was performed 12 (6–23) days after ILT. Six patients with breast cancer not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
(53 reference statements)
1
3
0
1
Order By: Relevance
“…Shin et al also demonstrated increased levels of IFN-γ between 2- and 4 weeks postoperation in 2 patients that underwent LITT 5 . This is consistent with the timeline of increased blood-brain barrier (BBB) permeability due to LITT presented by Leuthardt et al 2 Haraldsdóttir et al found that LITT-treated breast cancer patients experience increased lymphocyte infiltration within the tumor area and decreased T reg cells in regional tumor-free lymph nodes 9 . In vitro and mouse studies on hyperthermia and its effects on the anti-tumor immune response point to a need for a better understanding of how LITT may mechanistically impact immune responses in patients 1 …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Shin et al also demonstrated increased levels of IFN-γ between 2- and 4 weeks postoperation in 2 patients that underwent LITT 5 . This is consistent with the timeline of increased blood-brain barrier (BBB) permeability due to LITT presented by Leuthardt et al 2 Haraldsdóttir et al found that LITT-treated breast cancer patients experience increased lymphocyte infiltration within the tumor area and decreased T reg cells in regional tumor-free lymph nodes 9 . In vitro and mouse studies on hyperthermia and its effects on the anti-tumor immune response point to a need for a better understanding of how LITT may mechanistically impact immune responses in patients 1 …”
Section: Discussionsupporting
confidence: 56%
“…5 This is consistent with the timeline of increased blood-brain barrier (BBB) permeability due to LITT presented by Leuthardt et al 2 Haraldsdóttir et al found that LITT-treated breast cancer patients experience increased lymphocyte infiltration within the tumor area and decreased T reg cells in regional tumor-free lymph nodes. 9 In vitro and mouse studies on hyperthermia and its effects on the antitumor immune response point to a need for a better understanding of how LITT may mechanistically impact immune responses in patients. 1 Prospective clinical studies using LITT and immunotherapy will allow us to correlate these mechanisms to patient survival and optimize immunotherapy for GBM.…”
Section: Discussionmentioning
confidence: 99%
“…A number of pre-marketing clinical studies on imILT were performed at Lund University Hospital, Lund, Sweden, where the method was developed for the first time. These studies demonstrated the recruitment of immunocompetent cells in breast cancer patients which indicate a favorable antitumor activity [23][24][25][26][27].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…In patients with breast cancer, imILT induced an increase of CD8 lymphocytes within the tumor, an increase of mature CD83 DCs and CD20 B cells at the tumor border and a decrease of T reg lymphocytes in regional lymph nodes ( 84 ). Vogl and coworkers reported that laser-mediated thermotherapy of colorectal liver metastases induced a tumor-specific T cell stimulation (CD4, CD8) and increased cytolytic activity of T cells against an allogenic tumor ( 85 ).…”
Section: Local Tumor Destruction Methodsmentioning
confidence: 99%